O-18 Hosting a Darzi Fellow – one hospice and one fellow's experience. (19th November 2022) - Devlin, Jon; Humby, Kirsty
Abstract : Background/Aims: The Darzi Fellowship is a programme delivered by London South Bank University, designed to develop leaders from multi-professional backgrounds in their ability to undertake complex change initiatives that have a profound impact on them and the organisations they work for. Fellows study for a postgraduate leadership qualification, which involves taking on a challenge that involves leading complex change in systems in real time. Greenwich & Bexley Community Hospice has hosted a Darzi Fellow, who is part of the Darzi 13 cohort. The hosting arrangement is a collaboration between Greenwich & Bexley Community Hospice; the Health Innovation Network (HIN, who are the Academic Health Science Network for South London); and Guy's & St Thomas' NHS Foundation Trust. In practice, our Fellow has been splitting her time such that she has been supporting the hospice by working for approximately two days per week, splitting her remaining time between the HIN and the academic requirements of studying for a postgraduate qualification. It is unusual for hospices to be involved in the hosting of a Darzi Fellow and we will give insight into the benefits and potentials of this programme to our hospice now and to other hospices in the future. Methods/Results/Conclusions: We will share reflections and survey results from both our Fellow and from those she has worked with, in order to understand the impact of hosting an academic who is challenging the status quo within our organisation. We will share the benefits this partnership has had on the hospice in terms of providing greater opportunities to work across the local health and social care system, increasing the hospice's profile and understanding of the local population health and care needs. We will discuss how involvement with the Darzi Fellowship has supported opportunities for innovation and collaboration.